Intraoperative Magnetic Resonance Imaging–Guided Glioma Resections in Awake or Asleep Settings and Feasibility in the Context of a Public Health System - Angelo Pichierri; Marcus Bradley; Venkat Iyer (World Neurosurgery: X, 2019)
Background: Despite the most recent surgical aids and tools, surgical removal of infiltrating brain tumors remains a challenge. Unclear margins, edematous areas, and infiltrative behavior are the main causes for failing gross total removals. Also, excessive resection of peri-tumoral tissue often carries risks of damaging the nearby functioning cortical and subcortical structures with an unacceptable decrease in patient's quality of life and postoperative functional status, and the risk of making patients not eligible to adjuvant treatments. Awake surgery and intraoperative magnetic resonance imaging (ioMRI) are among the most effective aids in preventing damage to functional brain while maximizing the extent of resection. Methods: We present our series of 46 patients operated on at Southmead Hospital (North Bristol NHS Trust) in between July 2014 and February 2017 using ioMRI plus or minus awake surgery. Setting, patient features, indications, type and size of tumors, surgical times, extent of resection, morbidity, and survival are analyzed and discussed. Results: Overall, ioMRI check led to a +43% resections in Group 1 and +58% in Group 2. In grade 2 tumors, GTR was 46% in Group 1 and 55% in Group 2 (41% in control group). In grade 3 tumors, GTR was 57% in Group 1 and 66% in Group 2 (30% in control group). In Grade 4 tumors, GTR was 63% in Group 1, 66% in Group 2 (36% in control group). In terms of theatre occupation, the use of ioMRI added 1/2 operative session; the addition of awake surgery implied the use of another 1/2 operative session. Morbidity did not differ among the groups, with low incidence of permanent post-operative deficits (<5%). Group 2 OS was statistically longer when compared to the control group. Conclusions: Using ioMRI together with awake surgery is demanding for the anesthetic team, staff nurses, and for the patient. Nevertheless, low morbidity, greater total resections rates, and longer survival suggest its use is effective in making more approachable gliomas of all grades that we would consider “complex” due to their intrinsic features or locations. Key words: Awake surgery, Glioma, ioMRI, Neuro-oncology, Survival, Volumetric analysis